Analisis Penyajian Penyusunan Laporan Keuangan Pada Kejaksaan Tinggi Bengkulu Tahun 2022 - Khoirul Anwar; Neri Susanti; Nenden Restu Hidayah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
Each Government Agency Work Unit carries out accounting for economic transactions that occur within the managed budget, to produce financial reports that provide information that is accurate, relevant, and can be understood by stakeholders, such as the general public, financial institutions, and other stakeholders, with implement the principles that must be applied in presenting government financial reports, such as the principle of compliance, the principle of exact amount, the principle of consistency, and the principle of full disclosure, guided by Government Accounting Standards. This study aims to analyze the conformity of financial reports at Bengkulu District Prosecutor's Office with Government Accounting Standards Number 71 of 2010. Collecting data regarding the presentation of reports using descriptive comparatives in the form of case studies at Bengkulu District Prosecutor's Office. Writing uses interview techniques and documentation techniques to collect the necessary data. The results of the research show that Bengkulu District Prosecutor's Office. for Fiscal Year 2022 has carried out the process of presenting financial reports in accordance with Government Accounting Standards Number 71 of 2010 and has been presented and used by financial report user groups in decision making. This research is expected to have an important impact on the Bengkulu District Prosecutor's Office in improving the presentation of financial reports.